Hinduism, Critics of Hinduism and Revival of Hinduism in India’s Body Politic: An Exploratory Examination - Hasan, Rumy (South Asian Journal of Social Sciences and Humanities, 2022)
Though nominally a secular state, under BJP rule, Hinduism in India has seen a greater prominence in politics and society than at any time in the post-independence era. As such, it is worthwhile examining how, in certain core aspects, Hinduism may affect the key variables of economic and social development. This is a neglected area that has largely been ignored by international institutions, especially by UN agencies and the World Bank. This exploratory paper provides some historical context and focuses particularly on the impact of caste on India’s body politic and development. It examines the arguments of those that suggest that Hinduism may have positive effects and those that suggest otherwise. It concludes by arguing that negative effects far outweigh any putative benefits.